PENGARUH PERAN ORANGTUA SEBAGAI PENDIRI TERHADAP KEBERHASILAN WIRAUSAHA DI KELURAHAN HELVETIA TENGAH MEDAN TAHUN 2017 - Dicky Yuswardi Wiratna; Formaida Tambunan (Universitas Islam Negeri Sumatera Utara, 2017)
In general the entrepreneurial starts in the scope of a small family consisting of self-employment itself commonly referred to with the family business. The interconnectedness of the two institutions, families and businesses make the company describes several roles in family relationships that might help the parent company such as managerial as founder, the role of the brother, the role of entrepreneurial couples.The purpose of this research is to know the influence of parental role as the founder of the against the success of self-employment in the village Central Medan Helvetia. The data in this study consists of primary data obtained through questionnaires while the secondary data obtained through the Central Helvetia Village. This data was obtained processed and analyzed in order to be retrieved is there parental roles influence as founder against the success of self-employment in the village Central Medan Helvetia. The results of the analysis of the data obtained: 1) the role of parents as the founder of the majority with the role less as much as 47 (54%); 2) entrepreneurial Success by successfully as much as 51 majority (58.6%) 3) there is the influence of parental role as the founder of the against the entrepreneurial success (p = 0,004).